Answer:
The theorem is a²+b²=c²
Rewritten it is √(a²+b²) = c
Explanation:
The correct answer is: " c = √(a² + b²) " .
_________________________________________
Explanation:
_________________________________________
The Pythagorean theorem is: a² + b² = c² .
↔ c² = a² + b² ;
Take the square root of EACH SIDE OF THE EQUATION;
→ √(c²) = √(a² + b²) ;
→ c = √(a² + b²) ; which is one of the two answer choices given; which is correct.
_____________________________________________
Note: The other answer choice given:
m = (y₂ − y₁) / (x₂ − x₁) ; refers to the calculation of the slope of a line; given an equation for a line, in "slope-intercept form"; that is, "y = mx +b" ; in which "m" is the slope, given the coordinate of two points on the line:
________________________________________________
→ (x₁, y₁) ; and: (x₂, y₂) ;
_______________________________________
which is NOT related to the "Pythagorean theorem" equation.
__________________________________________________
Read more on Brainly.com - https://brainly.com/question/3726915#readmore